2013
DOI: 10.1108/arj-08-2011-0024
|View full text |Cite
|
Sign up to set email alerts
|

Audit quality and overvalued equity

Abstract: Purpose -Audit quality studies document that accruals decrease when the audit firm is large, or the audit firm is an industry specialist, or the audit-client tenure is long. The purpose of this paper is to posit that incentives related to highly-valued equity mitigate these results, as managers use income increasing accruals to augment earnings. Design/methodology/approach -To test this assertion, the authors regress discretionary accruals on: controls, a highly valued equity indicator variable equal to 1 if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…Assuming other variables are constant then the Big Four PAF will decrease the BTD value by 76833.83. The results of this study are in line with those of Tang and Firth [20] who found that BTD is able to detect earning management and the results of this study also support findings who found evidence that PAF with a good reputation can improve the quality of information as measured by the discretionary accrual value [10,23,[28][29][30]. Good audit quality can reduce the book tax difference because the auditor has an obligation to provide directed guidance on the responsibility of detecting fraud, without any exception on tax information in the financial statements (tax fraud).…”
Section: B Model 2 Testsupporting
confidence: 90%
See 1 more Smart Citation
“…Assuming other variables are constant then the Big Four PAF will decrease the BTD value by 76833.83. The results of this study are in line with those of Tang and Firth [20] who found that BTD is able to detect earning management and the results of this study also support findings who found evidence that PAF with a good reputation can improve the quality of information as measured by the discretionary accrual value [10,23,[28][29][30]. Good audit quality can reduce the book tax difference because the auditor has an obligation to provide directed guidance on the responsibility of detecting fraud, without any exception on tax information in the financial statements (tax fraud).…”
Section: B Model 2 Testsupporting
confidence: 90%
“…Further Rezaee stated that the phenomenon of the occurrence of fraud is the occurrence of earnings management by the company [27]. Some researchers found evidence that PAF with a good reputation can improve the quality of information as measured by the discretionary accrual value [10,23,[28][29][30]. Therefore, a good audit quality will be able to reduce book tax difference.…”
Section: = Tax Planning Aggressiveness Has a Positive Effect On Tax Smentioning
confidence: 99%
“…In this study, the quality audit was measured using the latest Proxy Audit Quality (PAQ 8) with 8 dummy measurements which were summed and divided by the total measurements. 8 proxies are developments from previous studies such as 1) Big 4, 2) Co-Statutory Auditor, 3) Audit Opinion, 4) Audit Lag, 5) Audit Specialization, 6) Big 4 & Co Statutory, 7) Audit Tenure, and 8) Experience (Kouba & Jarboul, 2017;Alfraih, 2016;Habib et al, 2014;Houmes et al, 2013;Dao & Pham, 2014).…”
Section: Variable and Measurementmentioning
confidence: 99%
“…At this stage, the role of auditors is necessary for investors to get their rights in receiving financial information company (Almutairi et al, 2009). By functioning as a controller, auditor qualified to suppress acts of earnings management by the company (Alhadab & Clacher, 2018;Asthana, 2014;Prawitt et al, 2009;Alzoubi, 2016;Huguet & Gandia, 2016;Rusmin, 2010;Rusmin et al, 2014;Zgarni et al, 2016) are also tax planning actions (Lin et al, 2012) resulting in the quality of financial statements (Alzoubi, 2018) according to regulations (Bepari, 2015) and have a good impact on performance (Hua et al, 2016) and firm value (Afza, 2014;Houmes et al, 2013;Khan et al, 2016),…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of auditing services carried out by auditors of the four largest accounting firms, namely Delloite Touche Tohmatsu, Price Water Coopers, Ernst & Young and KMPG (hereinafter referred to as the Big Four auditors), is able to contribute to the overvaluation, as their reputation and qualified specialized resources are capable of convincing the investors of a high quality of auditing by creating overvalued firm (Houmes et al, 2013;Wang et al, 2012;Houmes et al, 2013;Wang et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%